Answers

2014-06-22T23:20:44+05:30
43x+ 67y = - 24 and  67x + 43y = 24---------(1)
43x+67y=-24 or x=(-24-67y)/43-------(2)
Substituting(2) in(1),we get
67[(
-24-67y)/43]+43y=24
=>(-1608-4489y)/43+43y=24
=>-1689-4489y+1849y=24
=>-1689-2640y=24
=>1713=-2640y
=>y=1713/2640--------------(3)
putting this value of (3) in (2) we'll get value of x.
2 3 2
now u got bhargu
whom riasha is saying thanx
but the steps u did is not correct
no it is correct
i got the solutions from the net the value of x=1 and y=-1
2014-06-23T02:35:38+05:30
43x+ 67y = - 24 and  67x + 43y = 24---------(1)
43x+67y=-24 or x=(-24-67y)/43-------(2)
Substituting(2) in(1),we get
67[(
-24-67y)/43]+43y=24
=>(-1608-4489y)/43+43y=24
=>-1689-4489y+1849y=24
=>-1689-2640y=24
=>1713=-2640y
=>y=1713/2640--------------(3)
putting this value of (3) in (2) we'll get value of x. 
i hope u understood.....
plzzz mark my ans. as best
0